Knowledge of the Pasaman community in fulfilling nutritional needs in the first 1000 days of life - Meiyenti, Sri; Syahrizal, Syahrizal; Yunarti, Yunarti; Mitra, Robi (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
Malnutrition, especially the stunting category, is a big problem for the people in Pasaman today, because it has a broad impact on aspects of life which include health, social, culture and the economy. This study aims to identify the knowledge of the people in Pasaman about fulfilling nutrition at 1000 HPK and knowing the eating patterns of the Pasaman community at 1000 HPK. This study used qualitative research methods. Data was collected through participatory observation techniques and in-depth interviews. With the number of informants as many as 35 people. The results showed that in general, the community's knowledge of fulfilling nutrition in 1,000 HPK had received counseling and socialization from the village midwife and Posyandu cadres. However, this knowledge has not been seen in the people's diet at 1,000 HPK. The practice of daily eating patterns during the 1,000 HPK era was still the same as the habits that occurred before there was counseling. Food for pregnant and lactating women is prioritized is a matter of taste and preference, not about the nutritional content of food. Likewise with baby food 0-6 years, mothers already know that babies must be given exclusive breastfeeding, but there are still some mothers who do not give breast milk, because they think that breast milk is not filling for babies.